Deanery council in the Russian Orthodox Church at the beginning of the 20th century (materials from Yaroslavl diocese) - Dmitry Leonov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to study of deanery councils in Yaroslavl diocese of Russian Orthodox Church at the beginning of XX-th century. The author reveales the date of establishment of deanery councils (October 19, 1903) and analyzes the "Rules for Deanery Councils in the Yaroslavl Diocese". Special attention is paid to the changes of the regulatory framework of Deanery Councils and Deanery meetings during the period since 1903 to 1916. The article also explores the main directions of activity of Deanery Councils. The Deanery Council was a church governing body created to help the Dean. As a rule, the council consisted of a dean appointed by the diocesan leadership, and two members. The members of the council were elected at deanery meetings. On the scale of the entire Russian Church, Deanery Councils were established by the Local Council of 1917-1918, but in a number of dioceses they were created earlier. The clerical documents of the deanery councils of the Yaroslavl diocese have not been introduced into scientific circulation. Together with the reports of the deans, the journals of the meetings of the Yaroslavl general diocesan congresses of the clergy, materials from periodicals, these documents allow us to characterize the deanery councils as self-governing bodies of the clergy, which played a prominent role in the system of administration of the diocese. At their core, the Deanery Councils were the magistrates' courts for the clergy. They dealt with minor disciplinary offenses of clergy members, as well as civil disputes. The surviving documents make it possible to compose a picture of the most frequent offenses and disputes in the church environment. The documents also allow making a conclusion about dificult relationship between priests and the lower clergy - psalmists and deacons. In 1903-1916 the role of the lower clergy was increased in the activities of deanery councils and meetings. Since 1910 the psalmists and deacons had the voting right at deanery meetings. Archbishop Tikhon (Belavin) agreed at 1912 with the decision of the general diocesan congress of clergy: deacons and psalmists were included to the deanery councils.